Cell penetrating peptide grafting of PLGA nanoparticles to enhance cell uptake. (November 2018) - Feiner-Gracia, N.; Dols-Perez, A.; Royo, M.; Solans, C.; Garcia-Celma, M.J.; Fornaguera, C.
Graphical abstract: Schematic representation of the nanoparticles synthesis and functionalization process, together with a confocal microscopy image showing nanoparticle penetration in a model cell line. Highlights: Nano-emulsion templating: proper for thermosensitive compounds able to be scaled-up. Small NPs: formation of PLGA NPs from nano-emulsions smaller than most PLGA NPs. Versatility: CPP attachment without modifying NPs enables attachment of any peptide. Efficient uptake: only CPP-functionalized NPs show enhanced uptake in model cells. Abstract: Polymeric nanoparticles emerged a few decades ago and since then, their use and research has experienced an exponential increase, especially in the biomedical field. Among the methods to prepare polymeric nanoparticles, nano-emulsion templating is advantageous in terms of versatility, robustness, safety and efficiency. The current study represents a proof of concept of the versatility and robustness of this method for the formation of dell penetrating peptide (CPP) – functionalized PLGA nanoparticles able to efficiently cross plasma membrane and release their cargo inside the cell, where most active principles must perform their therapeutic activity. First, PLGA nano-emulsions were prepared by the phase inversion composition method, in mild conditions, required for labile pharmaceutical actives and without the need of purification steps, thus being appropriate for pharmaceutical purposes. Once nanoparticles are formed, they are functionalized, a posteriori, with a model CPP; procedure advantageous to preserve CPP functionality. It is worth noting that these nanoparticles showed smaller sizes than most PLGA nanoparticles reported previously elsewhere, property advantageous in terms of in vivo use. CPP covalent post-attachment promoted efficient nanoparticle uptake allowing them to efficiently cross plasmatic cell membranes, a bottleneck step for many nanosystems. Crossing plasmatic cell membrane was overcome with our CPP-functionalized nanoparticles, as confirmed by confocal microscopy studies. Thus, nanoparticles prepared by nano-emulsion templating can be considered a promising alternative to design novel efficient nanotherapies for multiple therapeutic purposes.